Metazoan Parasite Infracommunities in Five Sciaenids from the Central Peruvian Coast - Oliva Marcelo E; Luque José L (Memorias do Instituto Oswaldo Cruz, 1998)
Parasitological analysis of 237 Menticirrhus ophicephalus, 124 Paralonchurus peruanus, 249 Sciaena deliciosa, 50 Sciaena fasciata and 308 Stellifer minor from Callao (Perú) yielded 37 species of metazoan parasites (14 Monogenea, 11 Copepoda, 4 Nematoda, 3 Acanthocephala, 1 Digenea, 1 Aspidobothrea, 1 Eucestoda, 1 Isopoda and 1 Hirudinea). Only one species, the copepoda Bomolochus peruensis, was common to all five hosts. The majority of the components of the infracommunities analyzed are ectoparasites. The Brillouin index (H) and evenness (J´) were applied to the fully sampled metazoan parasite infracommunities. High values of prevalence and mean abundance of infection are associated to the polyonchoinean monogeneans; the low values of J' reinforce the strong dominance of this group in the studied communities. The paucity of the endoparasite fauna may be a consequence of the unstable environment due to an upwelling system, aperiodically affected by the El Niño Southern Oscillation phenomena.